2018
DOI: 10.1002/ajmg.c.31651
|View full text |Cite
|
Sign up to set email alerts
|

Genetics, genomics, and genotype–phenotype correlations of TSC: Insights for clinical practice

Abstract: Tuberous Sclerosis Complex (TSC) is a multisystem autosomal dominant condition caused by inactivating pathogenic variants in either the TSC1 or the TSC2 gene, leading to hyperactivation of the mTOR pathway. Here, we present an update on the genetic and genomic aspects of TSC, with a focus on clinical and laboratory practice. We briefly summarize the structure of TSC1 and TSC2 as well as their protein products, and discuss current diagnostic testing, addressing mosaicism. We consider genotype-phenotype correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 62 publications
1
64
0
4
Order By: Relevance
“…It was reported that TSC2 gene mutations are more common than TSC1 gene mutations (Peron et al, 2018a(Peron et al, , 2018b and that they are associated with an increased risk of seizures (Dabora et al, 2001). The fact that our patients had intractable epilepsy may partially account for our finding more TSC2 gene mutations than TSC1 gene mutations in our cohort.…”
Section: Discussionmentioning
confidence: 53%
“…It was reported that TSC2 gene mutations are more common than TSC1 gene mutations (Peron et al, 2018a(Peron et al, , 2018b and that they are associated with an increased risk of seizures (Dabora et al, 2001). The fact that our patients had intractable epilepsy may partially account for our finding more TSC2 gene mutations than TSC1 gene mutations in our cohort.…”
Section: Discussionmentioning
confidence: 53%
“…TSC2 mutations are usually related to a more severe phenotype than that in TSC1 mutations [20] . The ratio of TSC1 mutations in our study is lower than reported, and this may due to more patients with TSC1 mutations had milder phenotypes and patients with TSC2 mutations were more likely to seek treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Die Diagnose kann häufig anhand klinischer Kriterien gestellt werden [118], aber die Präsentation ist sehr variabel. Eine genetische Diagnostik ist zu empfehlen, wenn die Diagnose klinisch nicht eindeutig ist (besonders bei jüngeren Kindern), oder eine Relevanz zur genetischen Beratung weiterer Familienangehöriger besteht [119]. Nierenzysten sind nur ein Minor-Kriterium bei der klinischen Diagnose, ≥ 2 Angiomyolipome aber ein Major-Kriterium [118].…”
Section: Tuberöse Skleroseunclassified